The chondrite breccia of Antonin (L4‐5)—A new meteorite fall from Poland with a heterogeneous distribution of metal. (23rd August 2022) - Bischoff, Addi; Patzek, Markus; Peters, Stefan T. M.; Barrat, Jean‐Alix; Di Rocco, Tommaso; Pack, Andreas; Ebert, Samuel; Jansen, Christian A.; Kmieciak, Kryspin
Abstract: On July 15, 2021, a huge fireball was visible over Poland. After the possible strewn field was calculated, the first and so far only sample, with a mass of 350 g, was discovered 18 days after the fireball event. The Antonin meteorite was found August 3, 2021, on the edge of a forest close to a dirt road near Helenow, a small suburb of the city of Mikstat. The rock is an ordinary chondrite breccia and consists of equilibrated and recrystallized lithologies. The boundaries between different fragments are difficult to detect, and the lithologies are of petrologic type 5 and type 4. The rock is moderately shocked (S4) and contains local impact melt areas and thin shock veins. The low‐Ca pyroxene and olivine are equilibrated (Fs20.6 and Fa24.0, respectively), typical of L chondrites. The L chondrite classification is also supported by O isotope data and the results of bulk chemical analysis. The Ti isotope characteristics confirm that Antonin is related to the noncarbonaceous (NC) meteorites. One of the studied thin sections shows an unusual metal–chondrule assemblage, perhaps indicating that the metal in the chondrite is heterogeneously distributed, which is, however, not clearly visible in the element abundances.